BTRES: Beta-based Trust and Reputation Evaluation System for wireless sensor networks. (January 2016) - Fang, Weidong; Zhang, Chuanlei; Shi, Zhidong; Zhao, Qing; Shan, Lianhai
Abstract: Unlike traditional networks, the wireless sensor networks (WSNs) are very vulnerable to internal attacks from compromised nodes. The trust management system is the most effective way to defend the attack inside the network. The Beta-based Trust and Reputation Evaluation System (BTRES) is proposed in this paper for WSNs׳ node trust and reputation evaluation. BTRES is based on monitoring nodes׳ behavior, and beta distribution is used to describe the distribution of nodes׳ credibility. The node trust values are used to guide the selection of relay nodes, mitigating internal attacks risks. Simulation results show that the use of BTRES could effectively maximize the defense of internal attacks from compromised nodes and improve the WSNs׳ information security. In this paper, we mainly focus on the communication trust and data trust, and energy trust can be easily integrated into BTRES.